Factors associated with pregnancy outcome in anti‐TNF treated women with inflammatory bowel disease. Issue 4 (30th June 2014) - Seirafi, M.; de Vroey, B.; Amiot, A.; Seksik, P.; Roblin, X.; Allez, M.; Peyrin‐Biroulet, L.; Marteau, P.; Cadiot, G.; Laharie, D.; Boureille, A.; De Vos, M.; et al.
Summary Background The safety of anti‐tumour necrosis factor (TNF) agents during pregnancy is a major concern for child‐bearing women and physicians. Aim To assess the impact of anti‐TNF therapy on adverse pregnancy and foetal outcomes in women with inflammatory bowel disease (IBD). Methods Pregnancies occurring during anti‐TNF treatment or less than 3 months after its cessation in IBD patients followed in GETAID centres were recorded from January 2009 to December 2010. Ninety‐nine pregnancies in women without anti‐TNF treatment were identified from the CESAME registry. We compared pregnancy and neonatal outcomes by a case–control study. Results In the 124 IBD patients followed, 133 pregnancies were reported. At the conception time, 23% of patients had active disease. Eighty‐eight per cent (n = 117) of the 133 pregnancies followed until delivery resulted in 118 liveborns (one twin pregnancy). Complications were observed in 47 (35%) women and 24 (20%) newborns. In multivariate analysis, factors associated with pregnancy complications were: current smoking (P = 0.004), a B2 (stenotic) phenotype in CD women (P = 0.004), occurrence of a flare during pregnancy (P = 0.006) and a past history of complicated pregnancy (P = 0.007). Current smoking was the only factor associated with severe (i.e. potentially lethal) pregnancy complications (P = 0.02). Having IBD for more than 10 years prior to conception was associated with newborn complications (P = 0.007). No difference was found with the control group for any of the pregnancy and neonatal outcomes. Conclusion In our series, the safety profile of anti‐TNF therapy during pregnancy and the neonatal period appears similar to control group of IBD women not treated with anti‐TNF therapy.